A Companion to the Anthropology of Politics. - Nugent, David (Blackwell Companions to Anthropology, 2., 2008)
This Companion offers an unprecedented overview of anthropology's unique contribution to the study of politics.:.; Explores the key concepts and issues of our time - from AIDS, globalization, displacement, and militarization, to identity politics and beyond.; Each chapter reflects on concepts and issues that have shaped the anthropology of politics and concludes with thoughts on and challenges for the way ahead.; Anthropology's distinctive genre, ethnography, lies at the heart of this volume.